Influência da substituição parcial da areia por pó de vidro na produção de blocos de concreto - Souza, Marcos Ferreira de (2023)
The growing waste generation in recent decades shows that, along with this generation, waste management problems become evident. Categorically regarding glass waste, most of these are disposed of in landfills or dumps. Because it is a material that can be recycled indefinitely, as long as the separation is adequate, simply disposing of the glass is an unsustainable practice. For some types of glass packaging there is also the practice of return and reuse, however, comprising a small portion of packaging. The incorporation of waste in the manufacture of products used in civil construction has been studied, and the practice of using glass as a constituent of new products shows promising results. Studies indicate that the incorporation of glass can maintain or even improve many characteristics of cement artifacts, such as blocks, bricks, pavers, among others. Thus, the present work consists of two articles. The first of them, Chapter I, is a literature review on the post-use glass chain in the production of civil construction artifacts with the incorporation of glass, with the aim of presenting the state of the art of glass reuse in the manufacture of materials intended for construction. The works used in the review were searched in the Scielo, Science Direct, Periódicos Capes, etc. databases. The main keywords searched for articles were “glass”, “recycling”, “reuse”, “cement artifacts”. It is noticeable that the reuse of glass presents several scenarios, with or without improvement of the characteristics of the original products without glass. It is concluded that there is technical viability in some reuses of glass to replace the most used aggregates, such as sand, stone and cement, in different granulometries, replacement percentages, association with other waste, among others. In Chapter II, the results of the partial replacement of sand by waste glass from long neck bottles will be presented, at 25, 50 and 75% by mass, with granulometry smaller than 600 micrometers, in the manufacture of dry type concrete blocks. The results showed that the incorporation of glass in the blocks increased the resistance to simple compression and reduced the water absorption. Replacing sand with ground glass is technically feasible for the production of dry concrete blocks.